The role of intraoperative narrow-band imaging in transoral laser microsurgery for early and moderately advanced glottic cancer - Hanna Klimza (Brazilian Journal of Otorhinolaryngology, 2019)
Introduction: Trans-oral laser microsurgery is an established technique for the treatment of early and moderately advanced laryngeal cancer.Objective: The authors intend to test the usefulness of narrow-band imaging in the intraoperative assessment of the larynx mucosa in terms of specifying surgical margins.Methods: Forty-four consecutive T1-T2 glottic cancers treated with trans-oral laser microsurgery Type I-VI cordectomy were presented. Suspected areas (90 samples/44 patients) were biopsied under the guidance of narrow-band imaging and white light and sent for frozen section.Results: Our study revealed that 75 of 90 (83.3%) white light and narrow-band imaging-guided samples were histopathologically positive: 30 (40%) were confirmed as carcinoma in situ or invasive carcinoma and 45 (60%) as moderate to severe dysplasia. In 6 patients mucosa was suspected only in narrow-band imaging, with no suspicion under white light. Thus, in these 6 patients 18/90 (20%) samples were taken. In 5/6 patients 16/18 (88.8%) samples were positive in frozen section: in 6/18 (33.3%) carcinoma (2 patients), 10/18 (66.6%) severe dysplasia was confirmed (3 patients). In 1 patient 2/18 (11.1%) samples were negative in frozen section. Presented analysis showed, that sensitivity, specificity and accuracy of white light was 79.5%, 20% and 71.1% respectively, while narrow-band imaging was 100%, 0.0% and 85.7%, respectively.Conclusion: The intraoperative use of narrow-band imaging proved to be valuable in the visualization of suspect areas of the mucosa. Narrow-band imaging confirms the suspicions undertaken in white light and importantly, it showed microlesions beyond the scope of white light.